Optimized SM4 Hardware Implementations for Low Area Consumption - Ruolin Zhang; Zejun Xiang; Shasha Zhang; Xiangyong Zeng; Min Song (IET Information Security)
The SM4 block cipher is standardized in ISO/IEC, and it is also the national standard of commercial cryptography in China. In this paper, we propose two new techniques called “split-and-join” and “off-peak and stagger” to make SM4 more applicable to resource-constrained environments. The area optimization method uses a 1-bit data path while reducing the number of registers from 64 to 8 and the number of XOR gates from 194 to 8. As a result, we report a 1-bit-serial SM4 encryption circuit that occupies 1771 GE with a latency of 2,336 cycles. Additionally, the “off-peak and stagger” technique compresses all the operations within the state update and key schedule into 32 clock cycles to reduce the latency. In other words, it takes 32 clock cycles to complete one round encryption. The new circuit occupies 1861 GE with a latency of 1,344 cycles. Moreover, we also discuss how to further reduce the latency by increasing the data path with a small area overhead to provide wider area-latency tradeoffs for SM4. Our designs make SM4 competitive with many ciphers specifically designed for lightweight cryptography.